Arterial Function after a 246 km Ultra-marathon Running Race - Koutlianos, Nikolaos; Sotiriou, Panagiota; Christou, Georgios; Pagourelias, Efstathios; Anifanti, Maria; Christou, Konstantinos; Tsironi, Maria; Andriopoulos, Panagiotis; Kouidi, Evangelia; Deligiannis, Asterios (International Journal of Sports Medicine, 2021)
There is little research about the effects of ultra-endurance exercise on arterial morphological and functional properties. The aim was to assess the acute changes of the carotid-femoral pulse wave velocity and carotid doppler-derived parameters following an ultra-marathon race as well as the intima-media thickness of the carotid artery in ultra-marathon runners. Twenty athletes were examined at baseline and within 10 mins after a 246 km running race. Measurements included carotid-femoral pulse wave velocity, peak-systolic and end-diastolic velocities of carotid artery blood flow, pulsatility and resistivity indices and blood biochemical parameters. The intima-media thickness of the right and left carotid artery was measured before the race. Arterial stiffness and carotid artery intima media thickness at rest remained within known normal limits. The ultra-marathon race significantly increased carotid-femoral pulse wave velocity by 22.6% and pulsatility index by 10.2%. There was a decrease in body weight by 3.35% and an increase of all biochemical markers of muscle damage after the race. Additionally, C-reactive protein was correlated with both pulsatility and resistivity indices post-race. This study shows that immediately after a 246 km ultra-marathon running race, acute increase of arterial stiffness and vascular resistance were evident. The carotid artery thickness of ultra-marathon runners was within normal range.
Keywords: pulse wave velocity; carotid artery hemodynamics; ultra-marathon; arterial elastic properties; arterial stiffness